Knowledge, Action, Perception and Attitude of Management of Talangagung Landfill toward Edu-Tourism Program: A Community Perspective - Koderi Koderi; Suyadi Suyadi; Abdullah Said; Abdul Wahib Muhaimin (Program Pascasarjana, 2018)
This study aimed to determine the knowledge, action, perception, and attitude of landfill managers and community to Talangagung landfill program as an edu-tourism destination in Malang. Talangagung landfill became one of the best examples of waste management in Indonesia. This study used a quantitative approach by conducting field observations and questionnaire survey for data collecting. Questionnaires were distributed to community around landfill to assessed waste management in Talangagung landfill as an edu-tourism attraction. The data obtained was analyzed descriptive quantitatively by using Likert scale. The results showed that landfill manager and community had good knowledge about waste management practices based on environmental conservation principles. This was in line with the action, perception, attitude of landfill managers and community that supported the government program. The average Likert score of observed indicators indicated that respondents' answers were in the 'high level' category with a score of 3.92. It means respondents had a positive response to the questions posed by the researcher based on conditions in the field. Synergy and cooperation between landfill managers and community were one of the keys to support the success and sustainability of edu-tourism program in Talangagung landfill.Keywords: community, edu-tourism, landfill management, perspective.